Upaya Kepala Sekolah Dalam Meningkatkan Kinerja Guru Ekonomi Melalui Supervisi Klinis di Sekolah Menengah Atas Negeri 3 Ponorogo - Sasmito Pribadi (STIT Muhammadiyah Paciran Lamongan, 2022)
Clinical supervision as peer professional assistance is given to teachers who experience problems in learning so that the teacher concerned can overcome the problem by taking systematic steps including the planning stage, the stage of observing the behavior of the teaching teacher, as well as the stage of behavior analysis and follow-up. The research design to be carried out is to use School Action Research (PTS). The method of collecting data is through observation, field notes and documentation. The data analysis techniques used are: (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of the research are: the principal's efforts through clinical supervision are carried out on teachers, it can improve teacher performance as evidenced by increasing teacher performance from the beginning before the action by 58.2%, after the first cycle of action it becomes 70.1%, and after the second cycle of action it increases again to 83.7%. The results of research on clinical supervision of high-grade teachers have been shown to provide an increase in teacher performance which in turn has an impact on improving student learning outcomes.